Biomechanical Analysis of Mckenzie Method Therapy for Low Back Pain Patients - Nashrullah, Afif; Basri, Iqbal; Rafiah, Sitti; Walenna, Nirwana Fitriani; Walenna, Nirwana Fitriani; HN, Rustam (Journal of Neonatal Surgery, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal complaints and can interfere with daily activities. Various therapeutic methods have been developed to alleviate LBP symptoms, including the McKenzie Method and Core Stability Exercise. This study aims to analyze and compare the effectiveness of the McKenzie Method and Core Stability Exercise in reducing pain, improving range of motion (ROM), and decreasing disability levels in patients with LBP. This experimental study used a pretest-posttest control group design with a total sample of 33 patients diagnosed with non-specific LBP who met the inclusion criteria. The experimental group received McKenzie therapy, while the control group underwent Core Stability Exercise, each for 12 sessions (three times per week). Evaluations were conducted using the Oswestry Disability Index (ODI), Visual Analog Scale (VAS), and lumbar ROM measurements (flexion, extension, right and left lateral flexion). The results showed that both therapy methods were effective in reducing pain and improving mobility. However, the McKenzie Method demonstrated significantly greater improvements, especially after 12 therapy sessions (ODI p=0.001; VAS movement p=0.000; ROM extension p=0.005). McKenzie therapy also showed significant improvements in right and left lateral flexion and other functional aspects such as personal care, sitting, standing, and social life (p<0.05). Conversely, although CSE produced faster results in the early phase, its long-term effectiveness was relatively lower than that of the McKenzie Method. Therefore, the McKenzie Method is more recommended as a therapeutic option for managing LBP due to its ability to provide more optimal long-term recovery.